On a genaralized uniform zero-two law for positive contractions of non-commutative L1-spaces. (March 2016) - Ganiev, Inomjon; Mukhamedov, Farrukh; Bekbaev, Dilmurod
Abstract: In this paper we prove a non-commutative version of the uniform zero-two law for positive contractions of L 1 -spaces associated with von Neumann algebras.